Arthroscopic Scapholunate Capsuloligamentous Repair: Suture With Dorsal Capsular Reinforcement for Scapholunate Ligament Lesion - Vicente Carratalá, M.D. (Arthroscopy Techniques, 2017)
Scapholunate ligament (SLL) injury is the most frequent injury of the intrinsic carpal ligaments. The dorsal part of the SLL is the most important part for the stability of the scapholunate joint, and tears of this part and at least one of its secondary capsular attachments cause scapholunate dissociation. The arthroscopic technique most frequently used for acute injuries is reduction and fixation with Kirschner wires, and techniques that involve a primary repair of the injured ligament are performed by open surgery with efficient results. However, they lead to significant stiffness of the wrist due to injury to the soft tissue caused by damage to the secondary dorsal stabilizers; the dorsal blood supply; and in many cases, the proprioceptive innervation of the posterior interosseous nerve. We present an all-arthroscopic technique for the direct repair of acute injuries of the dorsal part of the SLL using bone anchors, complemented by a dorsal arthroscopic plication that reconstructs the dorsal capsulo-scapholunate septum of the scapholunate complex.